VIANA-ES NO SÉCULO XXI: O PROCESSO DE SEGREGAÇÃO SOCIOESPACIAL E OS INVESTIMENTOS PÚBLICOS - Honorato, Juliano Prata (2020)
This dissertation provides an understanding of how the production of privileged locations, highlights socio-spatial segregation and affirms the power of the State, as a reproducer of the interests of elites and an intensifier of the inequalities expressed